Disseminated infection due to Exophiala pisciphila in Cardinal tetra, Paracheirodon axelrodi - Řehulka, J; Kolařík, M; Hubka, V (Journal of fish diseases, 2017)
Cardinal tetra, Paracheirodon axelrodi (Schultz, 1956), kept in an ornamental tank, was found to be affected by severe invasive mycosis. Externally, the disease manifested as abdominal swelling, and internally, the anterior part of the intestine was extremely bloated with abundant dematiaceous septate hyphae and an accumulation of fluid. Histopathologically, a granulomatous inflammatory response was observed in the intestine wall, kidney and spleen. We assume that the mycotic agent was primarily deposited in the intestine and was then gradually disseminated to the other organs. DNA sequencing of ITS and LSU rDNA regions and phenotypic characterization were used for identification of the isolated fungus. The obtained data confirmed that the infection was caused by Exophiala pisciphila. The disease was subsequently reproduced in the carp fingerling using intramuscular and intraperitoneal injection of a spore suspension. The 13th day after intramuscular infection, a marked elevation of neutrophils was recorded in the peripheral blood; this involved a proliferation of band forms and segmented forms. As far as we know, this is the first report of infection due to E. pisciphila in Cardinal tetra.
Keywords: phaeohyphomykóza; Sequence Analysis, DNA; mezerníky ribozomální DNA; Animals; nemoci střev; DNA fungální; Phylogeny; Intestinal Diseases; nemoci ryb; DNA, Ribosomal Spacer; Exophiala; zvířata; sekvenční analýza DNA; DNA, Fungal; Fish Diseases; fylogeneze; Characidae; Phaeohyphomycosis